2021
DOI: 10.1155/2021/9952769
|View full text |Cite
|
Sign up to set email alerts
|

From the Urinary Catheter to the Prevalence of Three Classes of Integrons, β-Lactamase Genes, and Differences in Antimicrobial Susceptibility of Proteus mirabilis and Clonal Relatedness with Rep-PCR

Abstract: Introduction. Proteus mirabilis is a biofilm-forming agent that quickly settles on the urinary catheters and causing catheter-associated urinary tract infections. Thus, the spread of multidrug-resistant P. mirabilis isolates, with the ability to form a biofilm that carries integron, extended-spectrum β-lactamases (ESBLs), and plasmid-mediated colistin resistance genes (mcr), represents a severe threat to managing nosocomial infectious diseases. This study is aimed at surveying the prevalence of ESBL, integrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
2
15
1
Order By: Relevance
“…PCR condition was 3 min at 95°C; 30 cycles of 45 s at 94°C, 30 s at 50°C, and 45 s at 72°C; and finally, 5 min at 72°C. The PCR products were revealed by electrophoresis on a 1.5% agarose gel with 0.5x TBE at 3 hours with 60 voltage [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR condition was 3 min at 95°C; 30 cycles of 45 s at 94°C, 30 s at 50°C, and 45 s at 72°C; and finally, 5 min at 72°C. The PCR products were revealed by electrophoresis on a 1.5% agarose gel with 0.5x TBE at 3 hours with 60 voltage [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various molecular methods, such as repetitive extragenic palindromic PCR (Rep-PCR), pulse-field gel electrophoresis (PFGE), and ribotyping have been used to evaluate the genotypic diversity of several bacterial species [ 17 ]. Recent studies have shown that Rep-PCR is a reliable and fast tool for differentiating and typing gram-negative bacteria such as P. aeruginosa [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrofurantoin is bactericidal to a mean of 95% of E. coli UTIs (Brumfitt & Hamilton-Miller, 1998) and it is highly effective against S. saprophyticus isolates (Komp Lindgren et al, 2015) that made the resistance among E. coli to be lowest for nitrofurantoin (less than 1%) (Edlin et al, 2013;Kashanian et al, 2008) A study done on 68 bacteriologically proven simple UTI patients, concluded that K. pneumoniae isolates were highly resistant to nitrofurantoin (Rizwan et al, 2018), another study done on total of 1723 urine culture sensitivity reports of patients who were suspected to be having UTI, from July 2016 to Feb 2017 in a tertiary care hospital of Jharkhand, India concluded that all isolates of p. aeruginosa were absolutely resistant to nitrofurantoin and another study done in the microbiology section of the Central Laboratory of Tabriz University of Medical Sciences on 5136 outpatients suspected of having a UTI, also reported that all (100%) p. aeruginosa isolates were highly resistant to nitrofurantoin (Arabi et al, Kumar et al, 2017). Nitrofurantoin works by damaging bacterial DNA through interfering with the production of bacterial proteins, DNA, and cell walls of sensitive bacteria (McOsker & Fitzpatrick, 1994), while Klebsiella pneumoniae, Proteus mirabilis and pseudomonas aeruginosa are genetically resistant to nitrofurantoin (Brumfitt & Hamilton-Miller, 1998;Mirzaei et al, 2021). The finding of significant differences (P<0.05) between antibiotic brands and their standard discs may in most cases be due to the difference in physical nature, since the discs are dry while the antibiotics are liquid, resulting in scattering differences of spreading of the antibiotics in the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, each of these rules covered a diverse set of compounds, which is another evidence of the nuance in the molecular determinants of activity, which goes beyond selecting a given family or scaffold to produce active compounds. Rule 1 (the largest inactives rule) covers compounds from nine clusters (7,11,15,16,18,20,23,40,47) and rule 5 (the largest actives rule) covers compounds from 10 clusters (0, 2, 7, 8, 12, 17, 24,42,48,49). This means that the molecules defined by each anchor are structurally diverse but still have a similar Activity Cliffs, Substructural "Dead Ends", and "Safe Bets" in Urease Inhibitors.…”
Section: Chemical Space Visualization and Chemical Diversitymentioning
confidence: 99%